The importance of housing and neighbourhood resources for urban microbusinesses. Issue 6 (2nd June 2016) - Reuschke, Darja; Houston, Donald
ABSTRACT: Economic research has rarely considered the significance of the home and neighbourhood context of where business owners live for their business. Conversely, urban and neighbourhood research has overlooked how housing and neighbourhood shape business and entrepreneurship outcomes. This paper investigates the importance of housing and neighbourhood resources for microbusinesses using a random sample of microbusinesses in Edinburgh (UK) including those that are informal and home-based, and various characteristics of the neighbourhood in which the business owner lives were attached to the survey records. The data capture whether business owners have business premises outside their homes, and have used neighbourhood contacts, housing equity or space in the house for their business. In short, housing and neighbourhood resources are used by a large majority (82%) of microbusinesses. The findings challenge a number of common assumptions on the separation of commercial and residential functions, how neighbourhoods feature in the evolution of businesses, the nested conceptualization of home within a neighbourhood and on the nature of home-based businesses. It is concluded that multi-use (rather than mixed-use) neighbourhood planning would help foster more flexible and dynamic use of neighbourhoods and urban districts, although recognizing that this is a political issue.